1995
DOI: 10.1136/hrt.74.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipoprotein(a) concentrations are related to coronary disease progression without new myocardial infarction.

Abstract: Objective-To examine the association between serum lipoprotein(a) and angiographically assessed coronary artery disease progression without new myocardial infarction. Patients and design-85 patients with coronary artery disease who underwent serial angiography with an interval of at least two years were studied. Progression of coronary artery disease was defined as an increase in diameter stenosis of 15% or more. Vessels on which angioplasty had been performed were excluded from the analysis. The patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
(14 reference statements)
1
8
1
1
Order By: Relevance
“…However, other studies failed to demonstrate an association between Lp(a) and cardiovascular disease (29,30). In good agreement with our findings, Lp(a) levels showed a strong correlation with serial plaque progression assessed in previous angiographic (17)(18)(19)(20) and electron beam tomographic studies (21). Uchida et al (18) showed Lp(a) to be an independent predictor of angiographic lesion progression at 6 months follow-up, and Matsumoto et al (19) showed that the Lp(a) level was significantly associated with angiographic disease progression after more than 24 months.…”
Section: Multivariate Analysis Of Predictors Of Adverse Cardiovasculasupporting
confidence: 92%
See 1 more Smart Citation
“…However, other studies failed to demonstrate an association between Lp(a) and cardiovascular disease (29,30). In good agreement with our findings, Lp(a) levels showed a strong correlation with serial plaque progression assessed in previous angiographic (17)(18)(19)(20) and electron beam tomographic studies (21). Uchida et al (18) showed Lp(a) to be an independent predictor of angiographic lesion progression at 6 months follow-up, and Matsumoto et al (19) showed that the Lp(a) level was significantly associated with angiographic disease progression after more than 24 months.…”
Section: Multivariate Analysis Of Predictors Of Adverse Cardiovasculasupporting
confidence: 92%
“…There is evidence that plaque progression in coronary arteries is linked to a higher risk of future fatal or nonfatal cardiovascular events (15,16). Lipoprotein(a) is associated with plaque progression, as indirectly assessed by lumen changes in short-term (17,18) and long-term (19,20) angiographic follow-up, and with calcium score changes as measured by sequential electron beam computerized tomography (21). There are no data demonstrating directly the relation between Lp(a), fibrinogen, and coronary plaque progression.…”
mentioning
confidence: 99%
“…This is in agreement with previous angiographic studies suggesting that Lp(a) may be a risk factor for coronary artery disease. [7][8][9][10][11][12][13][14] The reason for the divergent results of Çömlekçi et al 15 is not known. The overall changes in the coronary and infarct artery scores during follow-up were not statistically significant, probably due to the short follow-up and modification of risk factors after infarction, as also indicated by the decrease in total cholesterol and LDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 98%
“…The overall changes in the coronary and infarct artery scores during follow-up were not statistically significant, probably due to the short follow-up and modification of risk factors after infarction, as also indicated by the decrease in total cholesterol and LDL cholesterol levels. Previous studies have shown that a high serum Lp(a) level is related to angiographic progression of coronary artery disease in patients without MI 11,12 but further studies in larger patient populations and with longer follow-up times are needed to clarify the role of Lp(a) in the progression of coronary artery disease immediately after MI.…”
Section: Discussionmentioning
confidence: 99%
“…29 Tamura et al examined the association between serum Lp(a) level and angiographically assessed coronary artery disease progression without new myocardial infarction, and reported a close association. 30 Igarashi et al reported that an elevated Lp(a) concentration is a significant predictor of long-term adverse outcome in AMI patients treated by primary percutaneous transluminal coronary angioplasty. 27 In this study, we demonstrated that coronary stenosis progression occurred and revascularizations for target restenotic lesions or new lesions were performed approximately 7 months after the onset of the first myocardial infarction in the patients who had serum Lp(a) ≥30 mg/dl; that is, CCSP occurred in a relatively short period after the onset of the first AMI in the high-Lp(a) patients.…”
Section: Lp(a) and Ccspmentioning
confidence: 99%